The Muslim Brotherhood in Europe: organisational and ideological transformation - Kondral, Aliaksandra A. (Journal of the Belarusian State University. History, 2020)
Political Islam has become an important factor of the international politics nowadays. By the beginning of the 21st century Islamist political groups have turned to be a matter of concern not only of the Middle East main stakeholders, but also the European and American ones. This circumstance has been aggravated even more, considering the fact, that, being a former metropolis, Europe had come to be a kind of cradle for the spread of Islam. The proportion of the Islamic population has been growing here year by year. Moreover, the migration waves following the 2011 Arab spring provoked even more tough migration crisis and posed a complicated challenge to the European society expressed in conciliation of freedom of religion within its Muslim community along with the preserving European values of secular democracy. The Society of the Muslim Brotherhood has always been considered to be a leading Islamist force not only in Arabic world but in the West as well. Indeed, if in the Middle East they position themselves rather as a political force, even though with wide representation, in Europe the Society of the Muslim Brotherhood claims to be a representative of the Muslim population of the region as a whole. Taking into account the growing Islamic presence in the continent, a certain anxiety in the European society cannot but exist, concerning the risk of conscious Islamic expansion. In this circumstances the question, whether this process is really taking place as well as which role the Society of the Muslim Brotherhood plays in it, came to the fore. This article tries to answer this question, analysing the different stages of the group’s ideological transformation and its influence on the group’s activity in Europe. The author comes to the conclusion, that being a movement, that has undergone substantial ideological transformation, the Society of the Muslim Brotherhood has followed a similar scenario in Europe. Since the organisation itself has made a long way from a militant organisation with anti-Western discourse to a moderate movement, claiming to be democratically oriented and tolerant to the West, their European branch has transformed from a small Islamist group in temporary exile in the enemy camp, to the organisation, considering itself a representative of the European Muslim community, as well as accepting Europe as a motherland.